Analisis Break Event Point Terhadap Perencanaan Laba CV. Uul Anugerah Surabaya - Zeni Rusmawati; Heru Budi Siswanto; Ma'ruf Sya'ban (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2018)
Break Even Point Analysis is an analysis that is used by the company to find out or planning on what the sales volume. The purpose of this study is to determine how determaining Break Even Point CV. Uul Anugerah Surabaya in 2011-2015 and to investigate the extent to which the role Break Even Point to the CV profit planning. Uul Anugerah Surabaya. The Conducted research approach is qualitative descriptive study, with data collection procedures used are interviews and documentation with data processing using descriptive analysis. Break Even Point has a significant role in the company, namely Break Even Point as a short-term planning tool, as a minimum sales information company, and as a tool for the development strategy to achieve the company's earnings. CV. Uul Anugerah management needs to maintain the achievement in 2011-2015 as well as the necessity of making a sales and costs per month as a material evaluation of progress made and the need for more promotions, more heavily in the consumer interest.